Media Contestation Efforts to Restructure DPR Recruitment (Comparative study of Computer Assisted Pattern ASN Recruitment Test/CAT) - Nashrillah; Datuk Imam Marzuki (Matondang Journal, 2024)
This research discusses media contestation to change DPR recruitment by comparing ASN recruitment using the CAT test. This research uses an approachcontent analysis method (Content Analysis). This analysis examines the content of written information in the mass media so that it is more correct, meaningful, meaningful or easier to accompany the audience's interpretation according to their perspective. The aim of the research is to provide information to the public that the CAT system has really been tested in recruiting ASN. If the recruitment of DPR members uses the CAT system, it does not use money politics and KKN. The quality of the DPR's performance will also be better in the future.